2017
DOI: 10.1371/journal.pone.0186179
|View full text |Cite
|
Sign up to set email alerts
|

TLR2/TLR4 activation induces Tregs and suppresses intestinal inflammation caused by Fusobacterium nucleatum in vivo

Abstract: Toll-like receptors (TLRs) 2 and 4 play critical roles in intestinal inflammation caused by Fusobacterium nucleatum (F. nucleatum) infection, but the role of TLR2/TLR4 in regulation of proinflammatory cytokines remains unknown. In this study, through microarray analysis and qRT-PCR, we showed that TLR2/TLR4 are involved in the F. nucleatum-induced inflammatory signaling pathway in Caco-2 cells, C57BL/6 mice and human clinical specimens. In TLR2-/- and TLR4-/- mice, F. nucleatum infection resulted in increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
32
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 26 publications
3
32
1
Order By: Relevance
“…Furthermore, many studies suggested that this phylum is associated with various clinical anaerobic infections (including in the mouth, teeth, gut, and brain) in humans, and is positively correlated with catarrhal appendicitis on the mucosal surface [38,39]. Within this phylum, the genus Fusobacterium plays a key role in promoting human colorectal cancer and various diseases in animals [40,41]. Fusobacterium nucleatum is important for the pathogenesis of various gut diseases, including intestinal inflammation and colon cancer [42].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, many studies suggested that this phylum is associated with various clinical anaerobic infections (including in the mouth, teeth, gut, and brain) in humans, and is positively correlated with catarrhal appendicitis on the mucosal surface [38,39]. Within this phylum, the genus Fusobacterium plays a key role in promoting human colorectal cancer and various diseases in animals [40,41]. Fusobacterium nucleatum is important for the pathogenesis of various gut diseases, including intestinal inflammation and colon cancer [42].…”
Section: Discussionmentioning
confidence: 99%
“…Fusobacteria , as typically dominant obligate anaerobic bacteria clustered in mouth, have been identified in a wide range of clinical anaerobic infections including oral, dental, gut and brain, and correlated positively with catarrhal appendicitis of mucosal surface 42 44 . Recently, it was reported that Fusobacterium plays a vital role in facilitating colorectal cancer 45 , and Fusobacterium nucleatum could definitely cause intestinal inflammation 46 . Perhaps the proportion increase of Fusobacterium in AP and DP could cause bowel inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…As we know, toll-like receptor 4 (TLR4) is a unique pattern recognition receptor (PRR), and TLR4 in the brain is mainly expressed in microglia (Seija Lehnardt et al 2003). Toxins in the brain can specifically recognize and combine with TLR4, activate the microglia and eventually lead to neuroinflammation (Jia et al 2017). Studies also indicate that TLR4 expression is significantly elevated in brain tissue of AD and PD patients and mice, and the aggregation of α-syn and Aβ is related to the activation of 5); AD-G, LPS + 10 9 CFU MG1363-pMG36e-GLP-1 group (n = 5); PD, MPTP group (n = 8); PD-G, MPTP + 10 9 CFU MG1363-pMG36e-GLP-1 group (n = 8).…”
Section: Discussionmentioning
confidence: 99%
“…In PD group, MPTP obviously increased the abundance of Proteobacteria, Cyanobacteria, Fusobacteria, Actinobacteria at the phylum level, increased the abundance of Enterococcus, Proteus at the genus level and markedly decreased the abundance of Akkermansia, Bilophila at the genus level. As we know, an increase in Fusobacterium nucleatum (F. nucleatum) promotes the production of the inflammatory factors IL-8, IL-1β and TNF-α, ultimately leads to intestinal epithelial inflammation (Jia et al 2017). Proteus mirabilis can cause motor dyskinesia, produce neuroinflammation and cause dopaminergic neuronal damage by producing LPS (Choi et al 2018).…”
Section: Discussionmentioning
confidence: 99%